Stigma and attitudes toward seeking counseling: A pilot study of cross-cultural differences between college students in the US and Cyprus - Zavrou , Sophia; Poulakis , Michael (Journal of Interdisciplinary Studies in Education, 2017)
The present study investigated differences between college students from Cyprus and a small, Midwestern university in the U.S. with regards to public and self-stigma towards seeking professional psychological help as well as help-seeking attitudes. Three ANCOVA tests, controlling for gender, were used to assess differences between the samples from the two countries. Participants from Cyprus reported greater public stigma toward counseling than participants from the U.S. did. However, the two groups did not differ in terms of self-stigma and attitudes towards seeking psychological help. Clinical implications in regards to public stigma and attitudes toward seeking counseling in Cyprus are discussed.